The Influence of Work Autonomy, Job Variation and Feedback on Job Satisfaction at PT Mas Arya Indonesia - Fitriana, Anisa; Mansyur, Anwar (Jurnal Ilmiah Sumber Daya Manusia, 2023)
The organization also continues to create conditions that can encourage employees to develop employee skills optimally. This study analyzes the relationship between work autonomy, job variations and job feedback on job satisfaction at PT Mas Arya Indonesia. The sample uses a census sampling of 198 employees. The results of multiple regression prove that work autonomy has no effect on job satisfaction, the variety of job variations and individual work feedback has a significant positive effect on job satisfaction. Work autonomy, variety of job variations and job feedback together can influence the level of job satisfaction by 95.5% while the remaining 4.5% is caused by other variables outside this study.